Analisis Faktor Determinan Ibu Hamil Resiko Tinggi Dengan Kek Di Puskesmas Kalibagor - Mu'minah, Ikhwah; Atmarina Yuliani, Diah; Purwo Aniarti, Reni (INVOLUSI: Jurnal Ilmu Kebidanan, 2025)
Pregnant women who do not get adequate nutritional needs will experience chronic energy deficiency. Pregnant women with chronic energy deficiency are pregnant women who are at risk of chronic energy deficiency, namely those who have an upper arm circumference below 23.5 cm or a pre-pregnancy body mass index or first trimester (gestational age ≤12 weeks) below 18.5 kg/ m2. Chronic lack of energy has an impact on the pregnancy process, causing anemia, stunted baby growth, during labor it will affect contractions (his) so that it will hinder the progress of labor, bleeding, low birth weight, and asphyxia. Cases of pregnant women with chronic energy deficiency must be treated intensively by health workers so that the mother's health condition can be well controlled to prevent complications that could occur and endanger the lives of the mother and fetus. Objective: Analyze the Determinant Factors for High Risk Pregnant Women with Chronic Energy Deficiency in the Kalibagor Community Health Center Work Area. Research type: This type of research is qualitative research with a phenomenological descriptive approach. Research results: The research results show that the cause of pregnant women experiencing chronic energy deficiency is due to a history of chronic energy deficiency and anemia from before pregnancy which was not handled properly. Apart from that, complaints of nausea and vomiting experienced by pregnant women as a form of discomfort during pregnancy result in a lack of nutritional intake containing balanced nutrition, thus having a negative impact on the health of pregnant women. Conclusion: Chronic energy deficiency in pregnant women needs serious treatment. Collaboration from various sectors is needed to overcome chronic energy deficiency in pregnant women. The role of midwives is very necessary for early detection of chronic energy deficiency starting from pre-conception so that chronic energy deficiency in pregnant women can be prevented. It is important to increase knowledge, especially among pregnant women, so that complications do not occur during pregnancy.